STUDYING THE INTERACTIONS BETWEEN MONOCYTES AND STAPHYLOCOCCUS AUREUS IN A MODELLED MICROGRAVITY ENVIRONMENT - Green, Macauley (2023)
Since the onset of space exploration, challenges to human health have been reported. Astronauts have suffered from various illnesses and ailments and prokaryotes have been found to thrive aboard spacecraft. Due to proposed missions to Mars and other long-term space habitation, exposure to the space environment is increasing. This leads to new biological, engineering and pharmaceutical challenges. By investigating changes to monocytes (first responders of the immune system) and Staphylococcus aureus (one of the most commonly found prokaryotes aboard spacecraft) in a proxy microgravity culture, the reasons for the decreased immune response and increased infection rate during spaceflight can begin to be understood. The aims in this thesis were to investigate the pro-inflammatory response of monocytes in microgravity to bacterial stimulation and understand how this affects their ability to deal with bacterial infection, investigate how changes to S. aureus virulence and colonisation phenotype regulation and expression are changed in microgravity culture, and how these microgravity changes interplay with each other in an in vitro infection model. It was first shown that microgravity culture leads to a reduction in cytokine production upon bacterial stimulation from both Gram-positive and Gram-negative sources and that an altered response, shown by upregulation of NF-κB translocation, occurs with regards to the transcription factors that regulate this from the Gram-negative stimulation. Inhibition of cytokine secretion was ruled out for the decreased cytokine production observed. Further studies showed that there was increased internalisation of S. aureus into monocytes in co-culture. Building on these findings, changes to S. aureus in microgravity were investigated and it was shown they have an increased colonisation factor phenotype expression and reduced virulence factor production due to reduction and delay of induction of the agr (accessory gene regulator) operon that regulates this. agr is part of the quorum sensing system in S. aureus and it was subsequently shown that the inducing molecule for this system, autoinducing peptide (AIP), had reduced production in microgravity culture. It was further shown however that interactions between this molecule and its’ receptor, AgrC, are unaffected in microgravity culture. Finally, the impact of microgravity induced changes on these two cell types were investigated with respect to interactions between each other in a microgravity co-culture, forming an in vitro infection model. From this the increased internalization of S. aureus was explored and visualised with fluorescent microscopy. From these results it was shown that both microgravity induced changes to monocytes and S. aureus are needed to cause the increased internalisation of S. aureus in monocytes that is previously reported. This was further confirmed with an S. aureus agr mutant strain. The novel findings of this work add to pre-existing knowledge of bacterial infection during spaceflight and highlights mechanisms such as agr-quorum sensing that have not been investigated previously.